Insulated piping

The use of weakly bonded ultrafine particle airgel powder with a three-dimensional network structure addresses the maintenance and cost issues of existing insulation technologies, achieving efficient and durable thermal insulation in double-layered pipes.

JP7603924B2Active Publication Date: 2024-12-23NAT INST FOR MATERIALS SCI +1
View PDF 26 Cites 0 Cited by

Patent Information

Application Number
JP2020193779
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-11-20
Publication Date
2024-12-23
Estimated Expiration
2040-11-20

AI Technical Summary

Technical Problem

Existing thermal insulation technologies for pipes with large temperature differences require costly maintenance, such as vacuum equipment or material replacement, and do not achieve optimal thermal conductivity or durability.

Method used

A double-layered insulated pipe using weakly bonded ultrafine particle airgel powder with a three-dimensional network structure composed of primary particles, optionally combined with hollow particles and a support mechanism, to reduce bulk density and thermal conductivity.

Benefits of technology

The solution provides high-performance thermal insulation at lower costs by reducing the weight and bulk density of insulation materials, minimizing maintenance needs, and enhancing thermal conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007603924000003
    Figure 0007603924000003
  • Figure 0007603924000004
    Figure 0007603924000004
  • Figure 0007603924000005
    Figure 0007603924000005
Patent Text Reader

Abstract

To provide a pipe for passing a fluid therethrough, with its outer wall in a double structure of inner and outer layers, wherein heat insulation is achieved in a space between the inner and outer layers with low cost and high performance.SOLUTION: A heat insulating pipe has a double structure of an inner pipe and an outer pipe. A heat insulator, loaded into a space between the inner pipe and the outer pipe, is made from an aerogel having a three-dimensional network structure with a skeleton formed of clusters being aggregates of primary particles, and includes fine particles having a three-dimensional network structure with a skeleton formed of the primary particles. A preferred form of such a heat insulator is a weakly-bonded ultra-fine particle aerogel powder that is produced by grinding, at extremely high speed, the weakly-bonded ultra-fine particle aerogel formed from an aerogel with aging conditions during the production process set at a low temperature and a short time period.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermally insulated pipe, and is particularly suitable for use in providing thermal insulation from the environment when a fluid passing through the thermally insulated pipe is at a low or high temperature. [Background technology]

[0002] For pipes that carry fluids such as liquids or gases, when the fluid is at a low or high temperature and there is a large difference in temperature between the fluid and the environment in which the pipe is installed, it is important to devise thermal insulation that can absorb the temperature difference.

[0003] Patent Document 1 discloses a thermally insulated pipe having an inner and outer double pipe (double piping) with a vacuum region provided in the space between the inner and outer pipes. Patent Document 2 discloses a thermally insulated pipe having a double piping in which the periphery of the inner pipe is covered with a microporous material.

[0004] Patent Document 3 discloses a double pipe (double piping) with an inner and outer pipe, containing a porous and elastic compressible material in the annular space between the outer pipe and the inner pipe. The annular space is said to contain the remainder of a container that previously compressed and held the compressible material. Examples of compressible materials that can be used include aerogel, silica aerogel, and nanoporous silica (e.g., claim 6).

[0005] Here, aerogel is a gel composed of a microporous solid whose dispersed phase is gas. For example, aerogel is produced by gelling a sol prepared by hydrolyzing and condensing a metal alkoxide dissolved in a medium to produce a wet gel, and removing the solvent component from the wet gel. In the wet gel, a three-dimensional network structure is formed using the particles contained as colloids in the sol as a raw material of metal alkoxide as a skeleton, and by removing the solvent component while maintaining the structure, a structure with fine pores is obtained. By preparing the size of the pores to be smaller than the mean free path of air, heat conduction through gas such as convection does not occur within the pores, and the thermal conductivity can be kept low. For this reason, aerogel is used as a thermal insulation material.

[0006] Patent Document 4 discloses an aerogel composite containing an aerogel component and hollow silica particles. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2000-081192 A [Patent Document 2] U.S. Patent No. 6,145,547 [Patent Document 3] International Publication WO2006 / 133155 [Patent Document 4] Patent No. 6288382 Summary of the Invention [Problem to be solved by the invention]

[0008] As a result of the inventors' investigation of Patent Documents 1, 2, 3 and 4, it was found that there existed the following new problems.

[0009] The technology described in Patent Document 1 requires an exhaust system to maintain the space between the inner and outer tubes in a vacuum. The illustrated double pipe is provided with an exhaust cylinder 7, which is connected to a suction system such as a vacuum pump via a sealing valve (paragraph 0012). This is because it is difficult to achieve a complete vacuum seal, and without exhaust, the degree of vacuum decreases over time, making it impossible to maintain the heat insulating effect. Such exhaust system is a cost factor.

[0010] In the technology described in Patent Document 2, the inner tube is covered with a microporous material to enhance the heat insulation effect while eliminating the need for an exhaust system, but the thermal conductivity of the microporous material is not as good as that of a vacuum, and the thermal insulation performance is also poor because there is a space between the outer tube and the microporous material. Furthermore, when the microporous material deteriorates over time, it requires periodic replacement and other maintenance, which is a cost factor.

[0011] In the technology disclosed in Patent Document 3, in order to completely fill the space between the inner and outer tubes, the material to be filled is limited to a porous, elastic, compressible material. The compressible material is sealed in a small container under reduced pressure, placed in the space between the inner and outer tubes, and then expanded and filled by releasing the reduced pressure (paragraph 0014, etc.). In addition, if the porous, elastic, compressible material deteriorates over time, maintenance such as periodic replacement is required, which is a cost factor, just like in the case of the technology described in Patent Document 2.

[0012] The aerogel composite disclosed in Patent Document 4 enhances heat insulation and flexibility by compounding hollow silica particles, but it is not expected to reduce the bulk density, and the amount used as an insulating material is a cost factor.

[0013] An object of the present invention is to provide a pipe through which a fluid passes, in which when the outer wall of the pipe is double-walled, thermal insulation is realized in the space between the inner and outer walls at low cost and with high performance. [Means for solving the problem]

[0014] According to one embodiment, the following is true.

[0015] That is, the present invention is an insulated pipe having an inner pipe, an outer pipe, a space between the inner pipe and the outer pipe, and an insulating material filled in the space, and the insulating material is made from an aerogel having a three-dimensional mesh structure whose skeleton is composed of clusters that are aggregates of primary particles, and is characterized in that the insulating material contains fine particles having a three-dimensional mesh structure whose skeleton is composed of the primary particles.

[0016] Here, primary particles will be explained. In the three-dimensional network structure of conventional aerogel powder particles, the units that constitute the skeleton are called secondary particles (see, for example, paragraph 0035 of Patent Document 4). A primary particle is a smaller unit particle that constitutes a secondary particle when multiple particles gather together. According to the same document, the diameter of a secondary particle is approximately 2 nm to 50 μm, while the diameter of a primary particle is 0.1 nm to 5 μm. However, as common technical knowledge, there is no universally uniform range for the absolute values ​​of the particle diameters of primary particles and secondary particles.

[0017] In this specification, aerogel fine particles having a three-dimensional network structure composed of primary particles are referred to as weakly bonded ultrafine aerogel powder. At this time, the weakly bonded ultrafine aerogel powder is produced by crushing an aerogel having a three-dimensional network structure composed of particles that are coarser than the secondary particles that compose the skeleton of the three-dimensional network structure of conventional aerogel, as described later. This aerogel having a three-dimensional network structure composed of particles that are coarser than the secondary particles of conventional aerogel is referred to as weakly bonded ultrafine aerogel. Effect of the Invention

[0018] The effects obtained by the embodiment are briefly described below.

[0019] That is, it is possible to provide a thermal insulation pipe in which the thermal insulation of the space between the inner and outer pipes when the pipes are doubled can be realized at low cost and with high performance. This is because the weight of the aerogel, which is the raw material of the thermal insulation material, can be reduced to a fraction of that of the conventional one. In the present invention, the skeleton of the three-dimensional network structure of the aerogel, which is the raw material of the thermal insulation material, is constructed using primary particles as units instead of the conventional secondary particles, and the aerogel (weakly bonded ultrafine aerogel) is pulverized into ultrafine powder (weakly bonded ultrafine aerogel powder). As a result, the bulk density of the weakly bonded ultrafine aerogel powder can be reduced to a fraction of that of the conventional aerogel powder, so that the weight of the aerogel required to fill the space between the inner and outer pipes can be reduced to a fraction of that of the conventional one. Here, the bulk density is the apparent density of the powder, and is calculated by dividing the mass of the powder when the powder is filled into a container of known volume by the volume of the container. The volume of the container includes not only the total volume of the particles that make up the powder, but also the gaps between the particles, and the bulk density also depends on the gaps between the particles that make up the powder. [Brief description of the drawings]

[0020] [Figure 1] FIG. 1 is an explanatory diagram showing a cross-sectional structure of a thermally insulated pipe according to the present invention. [Diagram 2] FIG. 2 is an explanatory diagram showing an overhead view of the configuration of the thermally insulated piping according to the present invention. [Diagram 3] FIG. 3 is an explanatory diagram that shows a typical structure of aerogel and a cut surface when it is crushed. [Figure 4] FIG. 4 is an explanatory diagram showing a schematic diagram of secondary particles that constitute the skeleton of the three-dimensional network structure of a typical aerogel. [Diagram 5] FIG. 5 is an explanatory diagram that shows a typical aerogel powder produced by pulverizing aerogel. [Figure 6] FIG. 6 is an explanatory diagram showing a schematic diagram of the three-dimensional network structure of the weakly bonded ultrafine particle aerogel produced after the aging step in the process of producing the weakly bonded ultrafine particle aerogel powder of the present invention. [Figure 7]FIG. 7 is an explanatory diagram showing a schematic diagram of secondary particles constituting the skeleton of the three-dimensional network structure of the weakly bonded ultrafine particle aerogel shown in FIG. [Figure 8] FIG. 8 is an explanatory diagram that shows a schematic cross section of the weakly bonded ultrafine particle aerogel shown in FIG. 6 when it is pulverized. [Figure 9] FIG. 9 is an explanatory diagram that illustrates the weakly bonded ultrafine particle aerogel powder of the present invention. [Figure 10] FIG. 10 is a flow chart showing an example of a method for producing the weakly bonded ultrafine particle aerogel powder of the present invention. [Figure 11] FIG. 11 is an explanatory diagram showing an example of control of the rotation speed of the crusher in the high-speed crushing process. [Figure 12] FIG. 12 is a distribution diagram showing the particle size distribution after the high speed milling process. [Figure 13] FIG. 13 is a graph showing the compression characteristics when vibration is applied to the experimentally produced weakly bonded ultrafine aerogel powder. [Figure 14] FIG. 14 is an explanatory diagram showing a cross-sectional structure of a thermally insulated pipe having a covered inner pipe. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] 1. Overview of the embodiment First, a summary of representative embodiments disclosed in the present application will be described. Reference numerals in parentheses in the summary of the representative embodiments refer only to components included in the concept of the components to which they are attached.

[0022] [1] Double-insulated pipe filled with weakly bonded ultrafine aerogel powder (Figs. 1, 2, 6, 7, 9) The insulated pipe (10) has an inner pipe (2), an outer pipe (1), a space between the inner pipe and the outer pipe, and an insulating material (3) filled in the space, the insulating material being made of aerogel (31) having a three-dimensional mesh structure with a skeleton formed of clusters (21) that are aggregates of primary particles (11) as a raw material, and containing fine particles (51) having a three-dimensional mesh structure with a skeleton formed of the primary particles. The fine particles (51) having a three-dimensional mesh structure with a skeleton formed of primary particles are weakly bonded ultrafine aerogel powder, and the raw material aerogel (31) is weakly bonded ultrafine aerogel.

[0023] This makes it possible to provide a thermally insulated pipe in which thermal insulation is achieved in the space between the inner and outer pipes when the pipes are double-layered, at low cost and with high performance.

[0024] [2] The majority of weakly bonded ultrafine aerogel powder has a dispersion peak with a particle size of 1 μm or less (Figure 12). In the thermal insulation pipe of item [1], 50% or more of the total number of the fine particles are dispersed with a mode of particle diameter of 0.1 μm to 1.0 μm. The particle diameter referred to here is the value observed by a laser diffraction type particle size distribution measuring device. In this specification, laser diffraction type particle size distribution measurement is abbreviated as PSD (particle size distribution) measurement. In this specification, particle diameter is explained on the premise of PSD measurement. However, in PSD measurement, not only the diameter of the particle itself but also the aggregation of particles is observed as the particle diameter, so the true particle diameter is likely to be smaller than the measured value. If there is a difference in particle diameter depending on the measurement method, please convert it to understand.

[0025] As a result, the bulk density of the weakly bonded ultrafine aerogel powder of the present invention is reduced to a fraction of that of conventional aerogel powder. Fine particles with a dispersion peak of 1 μm or less in particle diameter are considered to be fine particles (51) having a three-dimensional network structure composed of primary particles as a skeleton, and even if the dispersion peak is not sufficiently large, a certain effect of reducing the bulk density can be expected, but the effect becomes more noticeable when such fine particles account for a large number of particles.

[0026] [3] Addition of hollow particles (embodiment 2) In the thermally insulated pipe according to item [1] or [2], the thermal insulation material further contains hollow particles.

[0027] This allows the thermal conductivity of the insulating material to be reduced.

[0028] [4] Special gas enclosed within hollow particles (embodiment 2) In the thermally insulated pipe of item [3], the hollow particles have a shell, and a gas having a thermal conductivity lower than that of air is sealed in the hollow part inside the shell.

[0029] This allows the thermal conductivity of the insulating material to be further reduced.

[0030] [5] A special gas is sealed in the space between the inner and outer tubes (embodiment 3) In the thermally insulated pipe according to any one of items [1] to [4], a gas having a lower thermal conductivity than air is sealed in the space between the inner pipe and the outer pipe.

[0031] This can further improve the thermal insulation performance of the heat insulating material.

[0032] [6] Reducing pressure in the space between the inner and outer tubes (embodiment 3) In the thermally insulated pipe according to any one of the items [1] to [4], the space between the inner pipe and the outer pipe is reduced in pressure to a pressure lower than atmospheric pressure.

[0033] This can further improve the thermal insulation performance of the heat insulating material.

[0034] [7] Support mechanism for double piping (embodiment 3) The insulated pipe described in any one of items [1] to [6] includes a support mechanism fixed to the outer pipe to support the inner pipe, and the support mechanism is configured by bending a member that is longer than the linear distance between the inner pipe and the outer pipe.

[0035] This makes it possible to suppress heat conduction through the support mechanism connecting the inner pipe and the outer pipe, thereby improving the thermal insulation performance of the entire insulated piping.

[0036] [8] Reinforcement of the inner tube (embodiment 3) In the thermally insulated pipe according to any one of the items [1] to [7], the inner pipe is further covered with a member containing fiber.

[0037] This makes it possible to prevent accidents such as the inner pipe bursting even when high-pressure gas or liquid passes through the heat-insulated pipe.

[0038] 2. Details of the embodiment The embodiment will now be described in further detail.

[0039] [Embodiment 1] FIG. 1 is an explanatory diagram showing a cross-sectional structure of a thermally insulated pipe according to the first embodiment, and FIG. 2 is an explanatory diagram showing the configuration of the thermally insulated pipe from a bird's-eye view.

[0040] The thermally insulated pipe 10 according to the first embodiment is a thermally insulated pipe consisting of an inner pipe 2 and an outer pipe 1, and the inner pipe 2 is supported by a support member 4 attached to the inner wall surface of the outer pipe 1, forming an annular space between the inner pipe 2 and the outer pipe 1, and the annular space is filled with a thermal insulating material 3. As shown in Figs. 1 and 2, for example, three support members 4 are used to support the outer periphery of the inner pipe 2 at three points, and a set of three support members 4 are arranged at appropriate intervals in the longitudinal direction of the thermally insulated pipe 10.

[0041] The insulating material filled in the annular space between the inner tube 2 and the outer tube 1 includes weakly bonded ultrafine aerogel powder. Here, the weakly bonded ultrafine aerogel powder is made of aerogel having a three-dimensional network structure whose skeleton is composed of clusters, which are aggregates of primary particles, and is fine particles having a three-dimensional network structure whose skeleton is composed of the primary particles. This allows the insulating material filled in the annular space between the inner tube 2 and the outer tube 1 to be realized at low cost and with high performance. Here, the fine particles preferably have a particle diameter with a mode (peak) of dispersion of 1.0 μm or less, and more preferably, 50% or more of the total number of the fine particles have a distribution peak of 0.1 μm or more and 1.0 μm or less. This allows the bulk density to be reduced to a fraction of that of conventional aerogel powder, and therefore the weight of aerogel required to fill the space between the inner tube and the outer tube can be reduced to a fraction of that of conventional aerogel powder.

[0042] It is well known that aerogels with a three-dimensional network structure with fine pores can be produced by subjecting gels produced by the sol-gel method to supercritical drying or other methods. A sol produced by hydrolysis and condensation of a metal alkoxide solution is gelled to produce a wet gel, which is then aged and the solvent components are removed by supercritical drying to produce an aerogel. In a metal alkoxide solution, primary particles are dissolved in a solvent, and these primary particles condense with each other through hydrolysis and condensation to form a colloid. This is a gel, and the colloids formed are called secondary particles in contrast to the primary particles before condensation. In the gelled state, it is a wet gel containing solvent components. When the solvent components are removed from the wet gel by supercritical drying or other methods, a three-dimensional network structure consisting of secondary particles as units remains. This is the aerogel. Such aerogels are used by mechanically crushing them into powders of several tens of μm to several mm.

[0043] The weakly bonded ultrafine aerogel powder of the present invention is produced by producing a weakly bonded ultrafine aerogel with less aging than conventional aerogels, and pulverizing it at ultra-high speed. This results in a fine powder that is about 1 / 1000th of the fine powder produced when conventional aerogels are mechanically pulverized. More specifically, the weakly bonded ultrafine aerogel powder should have a mode (peak) of particle size distribution of 1.0 μm or less when observed by PSD measurement, and it is more preferable to produce it by pulverizing it at ultra-high speed under aging and pulverization conditions such that 50% or more of the total number of particles are dispersed with a mode of particle size of 100 nm or more and 1.0 μm or less. The particle size of the weakly bonded ultrafine aerogel powder observed by the inventors by PSD measurement is distributed with a mode of about 300 nm. Details will be described later.

[0044] Each particle of the weakly bonded ultrafine aerogel powder of the present invention has a three-dimensional network structure. Conventional aerogel powder particles also have a three-dimensional network structure, but the particles of the weakly bonded ultrafine aerogel powder of the present invention have a different unit that constitutes its skeleton. That is, as described in paragraph 0035 of Patent Document 4, "aerogel particle 1 is considered to be in the form of a secondary particle composed of a plurality of primary particles," the three-dimensional network structure of conventional aerogel powder particles is composed of secondary particles as units, whereas the particles of the weakly bonded ultrafine aerogel powder of the present invention are characterized in that the unit that constitutes its skeleton is a primary particle.

[0045] 3 to 5 are explanatory diagrams showing the structure of a general aerogel and aerogel powder produced by crushing the general aerogel. FIG. 3 shows the structure of a general aerogel 30 and a cut surface 40 when crushing the general aerogel, FIG. 4 shows secondary particles 20 constituting the skeleton of the three-dimensional network structure, and FIG. 5 shows aerogel powder 50 produced by crushing the aerogel 30 of FIG. 3. As shown in FIG. 3, in the general aerogel 30, the colloids contained in the gel before drying become secondary particles 20, and a three-dimensional network structure is formed with the secondary particles 20 as skeleton units. In the aerogel 30 produced in this way, the skeleton is formed in about 10% of the volume of the three-dimensional network structure, and the remaining about 90% is formed by pores. When the size of the pores is smaller than the mean free path of the gas that fills the pores, such as air, almost no heat conduction occurs due to collision of gas molecules. For this reason, aerogel is used as a thermal insulation material.

[0046] FIG. 5 shows a schematic structure of aerogel powder 50 when a general aerogel is crushed. When the general aerogel 30 shown in FIG. 3 is crushed, the cut surface 40 by the crusher is not the secondary particles 20 themselves, but the points where the secondary particles are connected. This is thought to be because the secondary particles 20 are densely aggregated primary particles 11 as shown in FIG. 4, so the bonds are strong, and the bonds between the secondary particles are much weaker. As a result, the aerogel powder 50 obtained when the general aerogel 30 is crushed has a three-dimensional network structure in which the skeleton is formed by the secondary particles 20 (FIG. 5).

[0047] 6 to 9 are explanatory diagrams showing the structure of the aerogel 31 after aging according to the present invention and the weakly bonded ultrafine particle aerogel powder 51 produced by pulverizing the aerogel 31. FIG. 6 shows the three-dimensional network structure of the weakly bonded ultrafine particle aerogel 31 produced after the aging process in the process of producing the weakly bonded ultrafine particle aerogel powder 51 of the present invention, FIG. 7 shows the secondary particles 21 constituting the skeleton of the three-dimensional network structure of the weakly bonded ultrafine particle aerogel shown in FIG. 6, FIG. 8 shows the cut surface 40 when the weakly bonded ultrafine particle aerogel 31 shown in FIG. 6 is pulverized, and FIG. 9 shows the weakly bonded ultrafine particle aerogel powder 51 of the present invention. In the present invention, the weakly bonded ultrafine particle aerogel 31 is produced by suppressing aging compared to the general process. Therefore, the three-dimensional network structure of the weakly bonded ultrafine particle aerogel 31 produced is formed with the skeleton of the secondary particles 21 (FIG. 7) in which the primary particles 11 are more loosely aggregated than in the past (FIG. 6). When the weakly bonded ultrafine aerogel 31 having such a three-dimensional network structure (FIG. 6) is subjected to ultra-high speed pulverization, not only the mutual bonds between the secondary particles 21 constituting the skeleton, but also the secondary particles 21 themselves have cut surfaces 40 by the pulverizer as shown in FIG. 8, and it is considered that the secondary particles 21 themselves are pulverized. As a result, the weakly bonded ultrafine aerogel powder 51 of the present invention has a three-dimensional network structure in which the skeleton is formed by the primary particles 11, as shown in FIG. 9. Since the secondary particles 21 are formed by loosely agglomerating the primary particles 11 as shown in FIG. 7, the outer edge of the actual secondary particles 21 is unclear, but in FIG. 8, the part corresponding to the outer edge is shown by a solid circle to facilitate understanding.

[0048] The inventors of the present invention noticed that the colloids produced during the production process of aerogel are formed by hydrolysis and condensation, and realized that by adjusting the aging conditions that govern the condensation reaction, it is possible to prepare aerogel with a three-dimensional network structure in which the skeleton is formed with primary particles as units, and arrived at the present invention. An example of the production method is described below.

[0049] FIG. 10 is a flow chart showing an example of a method for producing the weakly bonded ultrafine particle aerogel powder of the present invention.

[0050] Silica aerogel is mainly produced in two steps: forming a wet gel by the sol-gel method and drying the wet gel. The wet gel consists of a nanostructured solid silica network and a liquid solvent, and is produced by hydrolysis and condensation of silica precursor molecules. This silica precursor is produced by mixing TEOS (Tetraethoxysilane) and methanol (S1). A total of 6.3 g of oxalic acid (0.01 M) is then added to this mixture, and finally 1.5 g of ammonium hydroxide (NH 4 OH 0.5M) is added to form an alcosol, which gels when left at room temperature (S2).

[0051] Following gelation, the alcogels were aged in methanol at 60 °C for 3, 6, and 12 h, respectively (S3). Excessive amounts of methanol were added to the gels and then evaporated in a drying step at a temperature higher than room temperature. To avoid reverse reactions in the surface modification, the alcogels were immersed in hexane at 60 °C for 10 h, and the hexane-only solvent was replaced by a mixture of hexane and TMCS (Trimethylchlorosilane) to modify the surface (S4). Here, the volume ratio of hexane to TMCS was kept constant at 4. In the surface modification step (S5), the alcogels were immersed in a mixture of hexane and TMCS at 60 °C for 24 h. Before drying the alcogels, the samples were immersed in pure hexane at 60 °C for 6 h to remove excess TMCS (S6). The final step in creating the aerogels is drying (S7). The drying process consists of steps 1 to 3 and a cooling step. The first step was held at 40°C for 4 hours, the second step at 80°C for 2 hours, and the third step at 120°C for 1 hour, after which it was cooled together with the entire furnace.

[0052] After the drying steps (S4 to S7), the aerogel sample was subjected to a high-speed crushing step (S8). Using a Wonder Crusher WC-3 manufactured by Osaka Chemical Co., Ltd., a program was carried out three times with a crushing speed of 11,200 rpm to 21,000 rpm and a crushing time of about 5 minutes, as shown in FIG.

[0053] FIG. 12 is a distribution diagram showing the particle size distribution after the high-speed grinding process. For each sample with an aging time of 3 hours, 6 hours, and 12 hours, the particle size after the high-speed grinding process is plotted on the horizontal axis in a log scale, and the frequency (left vertical axis) and cumulative value (right vertical axis) of the relative particle amount are shown. For comparison, data on conventional (commercially available) aerogel powder is also shown. Here, the particle size was observed by PSD measurement. More specifically, FIG. 12 shows the results of measurement using a laser diffraction particle size distribution measuring device SALD-2300 manufactured by Shimadzu Corporation. Note that in PSD measurement, not only the diameter of the particle itself but also the aggregation of particles is observed as the particle diameter, so it is necessary to note that the measured value is biased in the positive direction (there are many errors in which a value larger than the true value is measured). However, as described below, sufficient information has been obtained to explain the characteristics of the weakly bonded ultrafine particle aerogel powder of the present invention.

[0054] In the conventional aerogel powder, the relative particle amount has only one peak with the average particle size of about 300 μm. In contrast, in the weakly bonded ultrafine aerogel powder of the present invention, the frequency of the relative particle amount after the high-speed grinding process has two peaks for the samples aged for 3, 6, and 12 hours. In the sample aged for 3 hours, the first peak has an average of 0.32 μm and a standard deviation of 0.10, and the second peak has an average of 21.14 μm and a standard deviation of 0.14. In the sample aged for 6 hours, the first peak has an average of 0.66 μm and a standard deviation of 0.15, and the second peak has an average of 31.89 μm and a standard deviation of 0.40. In the sample aged for 12 hours, the first peak has an average of 0.96 μm and a standard deviation of 0.13, and the second peak has an average of 38.52 μm and a standard deviation of 0.21.

[0055] The fact that the peaks are divided into two in this way strongly suggests that there is an essential difference between the particles that make up each peak. If there is no essential change and the diameter of the particles generated changes depending on the aging conditions, it is unlikely that two peaks would appear even if the position of the peak changes accordingly. Therefore, it is natural to think that the particles that make up the second peak, which has a large particle diameter, have a three-dimensional network structure with secondary particles as the skeleton unit as in the past, while the particles that make up the first peak, which has a small particle diameter, have a three-dimensional network structure with primary particles as the skeleton unit. That is, the results support the above explanation with reference to Figures 3 to 5 and Figures 6 to 9.

[0056] In addition, it can be seen that by changing the aging conditions, the properties of the particles generated after high-speed grinding, that is, whether the secondary particles or primary particles are the structural units of the skeleton, can be significantly changed, that is, controlled. The mode of the dispersion of the larger particle size is 10 μm or more, and the mode of the dispersion of the smaller particle size is 1 μm or less. In the samples aged for 6 hours and then pulverized at high speed, the cumulative value of the relative particle amount exceeds 50% on the side of the larger particle size peak. The cumulative value of the relative particle amount exceeds 50% on the side of the second peak when the particle size is about 20 μm in the sample aged for 6 hours and then pulverized at high speed, and when the particle size is about 40 μm in the sample aged for 12 hours and then pulverized at high speed, both of which are on the side of the second peak. On the other hand, in the sample aged for 3 hours and then pulverized at high speed, the cumulative value of the relative particle amount exceeds 50% on the side of the smaller particle size peak (first peak) when the particle size is about 0.3 μm. From another perspective, in the samples aged for 6 and 12 hours and then milled at high speed, 60% to 70% of the particles had a diameter of 10 μm or more, and their size indicates that most of the particles have secondary particles as their skeleton units, whereas in the weakly bonded ultrafine particle aerogel powder sample of the present invention aged for 3 hours, about 80% of the particles had a diameter in the range of 0.1 μm to 1.0 μm, that is, most of the particles have primary particles as their skeleton units, based on their size.

[0057] As for the aging conditions, in addition to shortening the time as described above, lowering the temperature is also effective. That is, the aging conditions for producing the weakly bonded ultrafine particle aerogel powder of the present invention are a temperature of 15°C to 70°C, more preferably 20°C to 70°C, and even more preferably 25°C to 60°C, a time of 0 to 24 hours, more preferably 0 to 12 hours, and even more preferably 3 to 12 hours, and the grinding parameters are a rotation speed of 10,000 to 30,000 rpm, more preferably 10,000 to 25,000 rpm, and even more preferably 11,000 to 22,000 rpm, and a time of 1 to 120 minutes, more preferably 3 to 60 minutes, and even more preferably 5 to 45 minutes.

[0058] The bulk density of the experimentally produced weakly bonded ultrafine aerogel powder was 0.018 g / cm 3 This is in line with the bulk density of commercially available aerogel powder, which is 0.06 g / cm. 3 ~0.20g / cm 3 The thermal conductivity is 1 / 3 to 1 / 11 of that of commercially available aerogel powder. On the other hand, the thermal conductivity is measured to be 23 mW / mK, which is the same level as the thermal conductivity of commercially available aerogel powder, which is about 23 mW / mK.

[0059] Figure 13 is a graph showing the compression characteristics when vibration is applied to the experimentally produced weakly bonded ultrafine aerogel powder. The experimentally produced weakly bonded ultrafine aerogel powder was placed in a container with a fixed base area, and vibration was applied to measure the change in aerogel height over time, and the graph shows a comparison with commercially available aerogel powder. The horizontal axis shows the vibration time in arbitrary units. The conventional aerogel powder reached a constant value at 82% of its initial height, whereas the experimentally produced weakly bonded ultrafine aerogel powder reached a constant value at 69%. Using this characteristic, the saturation point at which the bulk density is compressed due to changes over time is estimated to be 0.018 g / cm for the experimentally produced weakly bonded ultrafine aerogel powder mentioned above. 3 can be reduced by up to 0.026g / cm 3 On the other hand, according to the same theory, the bulk density of commercially available aerogel powder is about 0.12 g / cm 3 is a maximum of 0.13g / cm 3Although the difference is slightly smaller, there is still a ratio of 1:5. The weakly bonded ultrafine aerogel powder of the present invention has a bulk density that is a fraction of that of conventional aerogel powders, and requires a fraction of the amount of powder needed to fill the same space.

[0060] As described above, if the weakly bonded ultrafine aerogel powder of the present invention is used as a heat insulating material to be filled in the annular space between the inner and outer pipes in a double pipe, the bulk density is a fraction of that of conventional aerogel powder, so the cost of the heat insulating material required for filling can be significantly reduced. In addition, since the weakly bonded ultrafine aerogel powder is hydrophobic, there is almost no deterioration over time due to reaction with moisture remaining in the annular space, so the maintenance cost of periodically replacing the heat insulating material can be significantly reduced. Furthermore, since the weakly bonded ultrafine aerogel powder is very fine, it can be filled into every corner even if there is a narrowed part in the annular space between the inner and outer pipes, which greatly contributes to improving the thermal insulation performance of the heat insulating pipe.

[0061] [Embodiment 2] In the thermal insulation pipe 10 of the first embodiment, hollow particles may be further added to the weakly bonded ultrafine aerogel powder filled as a thermal insulation material in the annular space between the inner pipe 2 and the outer pipe 1. This can reduce the thermal conductivity of the thermal insulation material.

[0062] By using aerogel as a thermal insulation material, the size of the pores in the aerogel is smaller than the mean free path of air, so that heat conduction through the gas due to collisions of gas molecules or convection is suppressed, and thermal insulation performance close to that when the pores are a vacuum is expected. However, in reality, the performance does not reach that of a vacuum. As a result of the inventor's investigation into the cause, it was found that fine interconnected pores remain in the insulation material filled with aerogel powder, and the above-mentioned heat conduction occurs through these interconnected pores. Therefore, the inventors created a technology to reduce the thermal conductivity by adding hollow particles to the aerogel to hybridize it (patent application filed as Patent Application 2020-120921). The added hollow particles block the fine interconnected pores as described above, suppressing the slight heat conduction through the gas, and therefore the thermal conductivity can be reduced.

[0063] In addition, since the spherical shells constituting the hollow particles are highly airtight, the thermal conductivity of the insulating material can be further reduced by sealing a gas with a lower thermal conductivity than air inside the spherical shells.

[0064] The hollow particles to be added are not particularly limited, but may be nano-hollow particles, micro-hollow particles, or both. The nano-hollow particles are preferably prepared to have an outer diameter of 30 nm to 360 nm and a shell thickness of 7.5 nm to 65 nm. The outer diameter corresponds to a range of about 1 / 2 to about 5 times the mean free path of air at room temperature and normal pressure. In this way, the hollow size of the nano-hollow particles is prepared to be on the same order as the mean free path of air, so when added to aerogel, it contributes greatly to the heat insulating effect. The micro-hollow particles are preferably prepared to have an outer diameter of 1 μm to 23 μm and a shell thickness of 0.35 μm to 3 μm. The outer diameter is larger than 15 times the mean free path of air at room temperature and normal pressure, and in addition to contributing to the heat insulating effect, it has the effect of increasing the structural strength of the mesh. The fine interconnected pores described above remain in the aerogel, but the added hollow particles block these pores and suppress heat conduction through gas, such as convection, which occurs through the interconnected pores, thereby improving the insulating effect.

[0065] The hollow nanoparticles can be produced, for example, by the soft template method. That is, the surface of a polymer electrolyte is modified with ammonia in ethanol, and silica (SiO 2 By coating the core with a sintered material, particles consisting of a core and a shell are produced. By washing or sintering the core, the medium enclosed in the shell is removed, producing hollow particles.

[0066] For example, the double emulsion method is suitable for producing hollow microparticles. From a dispersed multiphase system consisting of an immiscible liquid such as an oil phase containing a surfactant and an aqueous phase consisting of a precursor and a surfactant, an emulsion containing droplets with the oil phase as the continuous phase and the aqueous phase as the center is produced by emulsification, and by adding aqueous phase to this, it is changed to an emulsion containing droplets with the gel as the center in the aqueous phase continuous phase. By washing / filtering or baking this, hollow microparticles are produced.

[0067] In the method for producing the weakly bonded ultrafine particle aerogel powder of the present invention, the hollow particles may be added to a mixture of TEOS and methanol prepared as a silica precursor (S1) before the gelation step (S2) in the flow chart shown in Figure 10. After the addition, the mixture may be sufficiently stirred by ultrasonic vibration to uniformly disperse the added hollow particles. The amount of hollow particles added is adjusted to the entire hybridized aerogel so as to have the following composition, for example.

[0068] The content of the hollow nanoparticles is preferably 0.01% to 30% by weight, more preferably 0.10% to 15% by weight, and most preferably 1.00% to 10% by weight. Similarly, the content of the hollow microparticles is preferably 0.01% to 30% by weight, more preferably 0.10% to 15% by weight, and most preferably 1.00% to 10% by weight.

[0069] As described above, in the insulated pipe 10, by adding hollow particles to the weakly bonded ultrafine aerogel powder that is filled as an insulating material in the annular space between the inner pipe 2 and the outer pipe 1, the thermal conductivity of the insulating material can be reduced.

[0070] [Embodiment 3] The insulated pipe 10 of the present invention may include a support mechanism 4 that is fixed to the outer pipe 1 and supports the inner pipe 2 (see Figs. 1 and 2). The support mechanism 4 is configured by bending a member that is longer than the linear distance between the outer pipe 1 and the inner pipe 2. The support mechanism 4 is configured to suppress heat conduction between the outer pipe 1 and the inner pipe 2 as much as possible while maintaining the mechanical strength between the outer pipe 1 and the inner pipe 2. Although not shown in the figure, a mechanism for connecting and supporting the outer pipe 1 and the inner pipe 2 may be provided at both ends of the insulated pipe 10, i.e., at the connection parts with other insulated pipes 10 or equipment such as a tank. In this case, it is preferable to configure the support mechanism by bending a member that is longer than the linear distance between the outer pipe 1 and the inner pipe 2 in order to suppress heat conduction at the connection parts.

[0071] The end of the insulated pipe 10 may be sealed so that the insulating material 3 to be filled does not leak out. The end of the insulated pipe 10 may be sealed after the insulating material 3 is filled in the annular space between the inner pipe 2 and the outer pipe 1. This makes it unnecessary to fill the insulating material 3 in the insulated pipe 10 during construction. On the other hand, the insulating material 3 may be filled after construction. In this case, a pipe that connects the annular space between the inner pipe 2 and the outer pipe 1 from the outside is provided in the insulated pipe 10 in order to fill the insulating material 3 in the insulated pipe 10 (not shown). Also, a pipe that discharges the filled insulating material 3 from the insulated pipe 10 to the outside may be further provided (not shown). This makes it easy to replace the insulating material 3.

[0072] As described above, the weakly bonded ultrafine aerogel powder of the present invention is pulverized at ultra-high speed to produce fine particles of about 300 nm, which is about 1 / 1000 of the size of conventional aerogel powder, so that even if there is a narrowed portion in the annular space, it can be filled to the end.

[0073] In the insulated pipe 10 of the present invention, the annular space between the inner pipe 2 and the outer pipe 1 can be filled with the insulating material 3 and can also be filled with a gas having a lower thermal conductivity than air. This can further improve the thermal insulation performance. The gas to be filled is preferably carbon dioxide. To fill the carbon dioxide, dry ice may be added when filling the annular space between the inner pipe 2 and the outer pipe 1 with the insulating material 3. The dry ice will evaporate and fill the annular space with carbon dioxide.

[0074] The annular space of the thermally insulated pipe 10 of the present invention may be depressurized while being filled with the thermal insulation material 3. In order to depressurize the space, the thermally insulated pipe 10 may be configured so that a pipe for evacuating the annular space and a vacuum pump can be connected to the thermally insulated pipe 10 (not shown).

[0075] In the insulated pipe 10 of the present invention, it is more preferable that the periphery of the inner pipe 2 is covered with a covering member 5 containing fibers. Fig. 14 is an explanatory diagram showing the cross-sectional structure of the insulated pipe 10 with the inner pipe 2 covered. When the fluid passed through the inner pipe 2 is a high-pressure gas or a liquid such as liquid hydrogen that may vaporize and become high pressure, accidents such as the rupture of the inner pipe 2 can be prevented. Suitable materials for the covering member 5 include, for example, glass fiber and carbon fiber.

[0076] The structure of the insulated pipe 10 suitable for the present invention is shown in Table 1 below. The insulated pipe of the present invention can be constructed with the inner pipe 2 and outer pipe 1 made of metal, plastic or polymer material, or a combination structure such as lamination of these. In particular, when transporting liquefied hydrogen, it is necessary to select an appropriate material for the inner pipe 2, for example SUS304L, SUS316 or SUS316L, taking into consideration resistance to hydrogen embrittlement. It is also preferable that the following specifications are satisfied. [Table 1] The specifications of the insulation material 3 suitable for the present invention are shown in Table 2 below. [Table 2] The invention made by the inventor has been specifically described above based on an embodiment, but it goes without saying that the invention is not limited thereto and can be modified in various ways without departing from the spirit of the invention. [Explanation of symbols]

[0077] 1 outer tube 2 Inner tube 3. Insulation 4 Support member 5 Covering material 10 Insulated piping 11 Primary particles 20 Secondary particles 21 Secondary particles formed by sparsely packing primary particles 30 Three-dimensional network structure formed by a skeleton of secondary particles 31 Three-dimensional mesh structure formed by a skeleton of secondary particles that are sparsely packed together by primary particles (weakly bonded ultrafine particle aerogel) 40 Cut surface by crusher 50 General Aerogel Powder 51 Weakly bonded ultrafine aerogel powder of the present invention

Claims

1. A thermally insulated pipe having an inner pipe, an outer pipe, a space between the inner pipe and the outer pipe, and a thermal insulating material filled in the space, The heat insulating material is made of aerogel having a three-dimensional network structure whose skeleton is composed of secondary particles, which are an aggregate of primary particles, and contains fine particles having a three-dimensional network structure whose skeleton is composed of primary particles generated by destroying the secondary particles, The fine particles are characterized in that, in their particle size distribution, 50% or more of the total number of particles are distributed in a particle size range of 0.1 μm or more and 1.0 μm or less, and have a mode in the particle range. Insulated piping.

2. A thermally insulated pipe having an inner pipe, an outer pipe, a space between the inner pipe and the outer pipe, and a thermal insulating material filled in the space, The heat insulating material is made of aerogel having a three-dimensional network structure whose skeleton is composed of secondary particles, which are an aggregate of primary particles, and contains fine particles having a three-dimensional network structure whose skeleton is composed of primary particles generated by destroying the secondary particles, The diameter of the particles constituting the heat insulating material is characterized in that the frequency distribution has two peaks including a peak due to the fine particles. Insulated piping.

3. In claim 1 or 2, The heat insulating material further contains hollow particles. Insulated piping.

4. In claim 3, The hollow particles have a shell, and a gas having a thermal conductivity lower than that of air is sealed in the hollow portion inside the shell. Insulated piping.

5. In any one of claims 1 to 4, A gas having a thermal conductivity lower than that of air is sealed in the space between the inner tube and the outer tube. Insulated piping.

6. In any one of claims 1 to 4, The space between the inner tube and the outer tube is depressurized to a pressure lower than atmospheric pressure. Characterized by: Insulated piping.

7. In any one of claims 1 to 6, The thermally insulated pipe includes a support mechanism fixed to the outer pipe to support the inner pipe, The support mechanism is configured by bending a member that is longer than the linear distance between the inner tube and the outer tube. The present invention is characterized in that Insulated piping.

8. In any one of claims 1 to 7, The inner tube is further covered with a material containing fiber. Insulated piping.

Citation Information

Patent Citations

  • Preparation method of silica aerogel particles with high daylighting rate

    CN104108720A

  • Method for preparing regular-appearance silicon dioxide aerogel particles by mechanical cutting

    CN105060309A

  • Method of preparing regular-shaped SiO2 aerogel granules through high-energy cutting

    CN105236421A

  • Prefabricated direct -burried steam insulating tube of urban heating

    CN208651968U

  • Aerogel heat insulation pipe filling device, aerogel heat insulation pipe and low-temperature smoking set

    CN209819048U